(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2026)
This study assessed the physicochemical parameters and heavy metal concentrations in the Balu River, an urban river that passes through Dhaka City. Water samples were collected from five sampling stations during the pre-monsoon, monsoon, and post-monsoon seasons from October 2021 to September 2022. River water controlling parameters such as temperature, pH, EC, TDS, DO, BOD, NO₃⁻, NH4⁺, SO₄²⁻, PO₄³⁻, and heavy metals such as Pb, Cd, Cu, Mn, and Cr from the Balu River were monitored seasonally. The study showed seasonal variations in temperature (26.4 to 30.8°C), pH (7.12 to 7.63), EC (144.2 to 571.0 µS/cm), TDS (304.8 to 878.0 mg/L), DO (2.25 to 3.08 mg/L), and BOD (21.69 to 24.92 mg/L). The high BOD and low DO content indicated organic pollution, while elevated EC and TDS suggested significant inorganic contamination. The nutrient (NO₃⁻, NH₄⁺, SO₄²⁻, PO₄³⁻) levels also varied, with concentrations peaking in the post-monsoon season. Heavy metals Pb (0.010 to 0.063 ppm), Cd (0.0013 to 0.0091 ppm), Cu (0.021 to 0.071 ppm), Mn (0.032 to 0.108 ppm), and Cr (0.018 to 0.095 ppm) revealed that they were within the permissible limits set by the Environment Conservation Rules (ECR). However, metal concentrations were highest in the post-monsoon season. Despite being below critical pollution thresholds, the cumulative impact of pollutants and heavy metals compromised the river’s suitability for aquatic life, irrigation, and drinking. Industrial waste discharge was identified as the primary cause of degradation. The study highlights the need for stringent monitoring and mitigation efforts to protect the river’s ecosystem. Int. J. Agril. Res. Innov. Tech. 15(2): 85-97, Dec 2025